The Inhibitory Effect of Resveratrol on Elastin Amyloidogenesis. (13th May 2014) - Pepe, Antonietta; Delaunay, Florian; Bracalello, Angelo; Bochicchio, Brigida
Abstract : The role of polyphenols in the prevention of degenerative diseases is emerging in the last years. In this report, we will investigate in vitro the inhibitory effect of resveratrol on elastin amyloidogenesis. The effect of resveratrol on molecular structure was investigated by circular dichroism spectroscopy, while the inhibitory effect on self-assembly was evaluated by turbidimetry as a function of temperature and by atomic force microscopy.